(untitled) (Community Based Medical Journal, 2018)
Pleural effusion is common medical problem in clinical practices. Because extensive investigation is needed for diagnosis of pleural effusion especially exudative pleural effusion. But in some cases it remains undiagnosed. Parapneumonic effusion more common in younger age, in developed countries tubercular pleural effusion is common in all age group. Above 60 years malignant pleural effusion is suggested. This cross sectional study was conducted on department of respiratory medicine and department of Medicine in Dhaka Medical College Hospital (DMCH) during the period of January 2017 to July 2017. Clinically suspected 100 patients were enrolled in this study. Aetiology of pleural effusion was confirmed by clinical and laboratory diagnosis like x-ray, cytology, biopsy. This study showed 28(28%) were diagnosed as parapneumonic pleural effusion, 47(47.0%) as tubercular pleural effusion which was confirmed by ADA level and gene expert, 14(14%) were malignant pleural effusion was confirmed by histopathology of biopsy material and 11(11%) as undiagnosed pleural effusion. Among malignant pleural effusion, adenocarcinoma was 71.42%, large cell carcinoma was 14.28% , both small cell carcinoma and mesothelioma is 7.14%. CBMJ 2018 January: Vol. 07 No. 01 P: 30-34